The seemingly impossible love life of Amanda Dean - Rose, Ann (Ann M.) (Berkley Romance, 2024)
"It's her wedding day and it'll be the happiest day of her life...won't it? Amanda Dean would say she's an okay artist and a loyal friend, but what she's best at is falling in love. A self-proclaimed bi disaster who has had her heart broken more times than she cares to count, Amanda can't help opening herself up. As she gets ready on the day she's waited a lifetime for, memories of her past loves run through her mind, with one glaring red sign blinking above them-is this "the one"? Will it be: the fit water polo player, the fashionista, the dependable hedge fund manager, or the one where the timing was never quite right. Now, on the day of her wedding-a day where everything already seems to be going wrong-Mandy must decide if she's willing to risk it all one last time or if she'll escape while her whole heart is still intact. Equal parts heartwarming and bittersweet, The Seemingly Impossible Love Life of Amanda Dean expertly weaves the wonder and terror of falling in love into a beautifully crafted story about the joy that can be found when you're willing to dust yourself off and try again"--